CORRELATION STUDY BETWEEN FREQUENCY OF WATCHING ATTACK ON TITAN AND READING COMPREHENSION - Saputra, Teguh; Bunau, Eusabinus; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to measure the correlation between students’ frequency of watching Attack on Titan with their reading comprehension of third-semester Student of English Language Education Study Program Tanjungpura University Academic Year 2018/2019. The problem of this research was design to investigate the correlation between two variables. This research applied correlation method. The sample was 30 students of three semesters. The technique to collect the data was measurement technique. The form of test was multiple choices consist of 30 items of reading comprehension. The hypothesis was tested by using t-test formula. The result of this calculation shows that t-observed was 7.08, it is higher than t-table 2.46 with df= n-2 (28) in level of significance 0.01. It means that the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. Finally, The result of the calculation showed that the value of coefficient correlation between students’ frequency of watching Attack on Titan and their reading comprehension was 0.80. In conclusion, the students' frequency of watching Attack on Titan has positive correlation with their reading comprehension.000Key words: Classroom Action Research, Reading Comprehension, Recount Texts, Reciprocal Teaching Technique